Isosceles Trapezoid with Integer Area: Cryptographic Applications ofGeneralized Pell-Type Equations and Sphenic Numbers - Deepshika, A; Kannan, J; Mahalakshmi, M (Optimality, 2025)
The well-known generalized Pell equation, x2 − dy2 = n, was used to develop the algorithm in this study. d was fixed as a prime number, and n was the square of the sphenic number. In particular, we employ the assignments utilizing the area of the isosceles trapezoid with the non-parallel sides being 2n − 1 and the parallel sides being n and n + r.